Diagnosis of secondary peripheral neurolymphomatosis: a multi-center experience. Issue 11 (2nd November 2017) - Byun, Ja Min; Kim, Ki Hwan; Kim, Miso; Kim, Tae Min; Jeon, Yoon Kyung; Park, Jeong Hwan; Paik, Jin Ho; Lee, Jung Min; Lee, Ho-Young; Lee, Jong Seok; Heo, Dae Seog; Lee, Jeong-Ok
Abstract: Here, we describe our experience with secondary neurolymphomatosis (NL) in non-Hodgkin lymphoma patients, with the emphasis on the diagnosis process. A retrospective chart review of 12 patients from 3 tertiary academic centers between January 2005 and December 2015 was conducted. Secondary NL was diagnosed within a median interval of 10 months (range 5–41 months) after initial diagnosis of NHL. Painful neuropathy was present in 66.7%, but the diagnosis of NL was delayed in nine out of 12 patients (75.0%) by median of 2 months. Diagnostic modalities included CSF analysis performed in nine patients (75.0%), electrodiagnostic studies in seven (58.3%), radiologic studies in all, and nerve biopsy in two (16.7%). The diagnostic yield was 100.0% (15/15) for FDG-PET/CT and 75.0% (9/12) for MRI. Our experience emphasizes the importance of clinical suspicion of NL in patients with previous history of NHL and selection of diagnostic modality with the greatest clinical utility.